Optic nerve head anatomy in myopia and glaucoma, including parapapillary zones alpha, beta, gamma and delta: Histology and clinical features - Wang, Ya Xing; Panda-Jonas, Songhomitra; Jonas, Jost B. (Progress in retinal and eye research, 2021)
The optic nerve head can morphologically be differentiated into the optic disc with the lamina cribrosa as its basis, and the parapapillary region with zones alpha (irregular pigmentation due to irregularities of the retinal pigment epithelium (RPE) and peripheral location), beta zone (complete RPE loss while Bruch's membrane (BM) is present), gamma zone (absence of BM), and delta zone (elongated and thinned peripapillary scleral flange) within gamma zone and located at the peripapillary ring. Alpha zone is present in almost all eyes. Beta zone is associated with glaucoma and may develop due to a IOP rise-dependent parapapillary up-piling of RPE. Gamma zone may develop due to a shift of the non-enlarged BM opening (BMO) in moderate myopia, while in highly myopic eyes, the BMO enlarges and a circular gamma zone and delta zone develop. The ophthalmoscopic shape and size of the optic disc is markedly influenced by a myopic shift of BMO, usually into the temporal direction, leading to a BM overhanging into the intrapapillary compartment at the nasal disc border, a secondary lack of BM in the temporal parapapillary region (leading to gamma zone in non-highly myopic eyes), and an ocular optic nerve canal running obliquely from centrally posteriorly to nasally anteriorly. In highly myopic eyes (cut-off for high myopia at approximately -8 diopters or an axial length of 26.5 mm), the optic disc area enlarges, the lamina cribrosa thus enlarges in area and decreases in thickness, and the BMO increases, leading to a circular gamma zone and delta zone in highly myopic eyes.